A study on the effectiveness of casein phosphopeptide-amorphous calcium phosphate on remineralization of white spot lesions on tooth surface of orthodontic patients in the University of the Philippines College of Dentistry Post-Graduate program in Orthodontics - De Vera, Jhomileen C.; Paez, Gemmeritz D.; Santos, Jessica R. (Adviser).
This study aimed to determine the effectiveness of Casein Phosphopeptide-Amorphous Calcium Phosphate (CPP-ACP) in reversal of white spot lesions on tooth surfaces of orthodontic patients. Sixteen lesions were noted during the pre-screening but by the start of the study only 14 lesions were noted. Out of 14 lesions, 8 were assigned to the experimental group and 6 for the control group. Results showed that for the assessment in the changes of white spot lesion after one month in the experimental group, only two lesions were observed while in the control group, no reduction was observed. For the experimental group, statistics showed that there is a significant decrease in the number of white spot lesions, while for the control, statistics showed that there is no significant evidence to say that there is a decrease in the number of white spot lesions. For the comparison of the performance of the experimental and control group in reducing white spot lesion, results showed that the experimental group is better than the control in removing white spot lesions. Hence, CPP-ACP is effective in reversal of white spot lesions on tooth surfaces of orthodontic patients.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Tooth -- Remineralization